O gasto real com medicamentos para diabéticos e hipertensos comparado ao gasto registrado no sistema de informação hiperdia em município de pequeno porte - Guilherme, Renata Silva (2011)
The impact of spending on medicines in Brazil is consistent with that seen in most developing countries, to consume up to one third of resources to health care. In view of ensuring the constitutional principles of universality, fairness and integrity of action, the Unified Health System uses tools that provide efficiency in the use of resources, the provision of safe and effective drugs, and in its proper employment. Funding for the Drug Assistance part of the three spheres of government, directly depending on the joints due to their managers in order to innovate the Public Policy, focused on the need for its region, with priority interest to local needs without losing the parameters established by the SUS. In the municipality of that expense is Herculândia around. To provide full access to the medicines of primary care or essential drugs, the delivery must be undertaken in a rational way. This work aims to relate the consumption of drugs by tablet and financial expense for patients enrolled in the program for hypertension and diabetes (Hiperdia) technical protocol as compared to actual consumption in tablets and financial expense occurred in the dispensaries of medicines from USF. In 2007 recorded 910 people were registered in Hiperdia, and medicines used in health care units in the city for treatment of hypertension are Captopril 25mg, propranolol 40mg, 25mg Hydrochlorothiazide (hct), Alfametildopa 250mg, and diabetes are glibenclamide 5mg, insulin NPH and metformin 850mg. It can be observed that in all of the expense items were differences according to the ideal Hiperdia, and the actual expenditure vary across the products. As the cost of drugs based on consumption, whereas the dose reached the maximum dose in all the requirements, it was noted that the quantity of all items exceeded the maximum dose recommended by the protocols. In addition to excessive spending with medicines, there was a wide variation in the consumption of items every month.